EPDM/PE-based thermoplastic vulcanites : crosslinking chemistry and dynamic vulcanisation along the extruder - Duin, M. van (2005)
This paper presents new insights in the resole crosslinking chemistry of thermoplastic vulcanisates (TPVs) and in the production of TPVs on extruders. Low-molecular-weight olefins were used in combination with EPDM crosslinking experiments to investigate the resole crosslinking chemistry. The fact that enhanced substitution of the olefin/EPDM unsaturation enhances the reactivity towards the resole strongly supports the cationic character of SnCl2-activated resole crosslinking. Samples were collected along the extruder during TPV preparation to study the physico-chemical phenomena during compounding. It was observed that crosslinking of the EPDM phase takes place even when the PE phase is not yet fully molten. Upon complete melting of the PE phase the blend very quickly reaches its final morphology. Only for the (50/50; w/w) blend, a transition from continuous via co-continuous to fully dispersed EPDM is observed, which is driven by crosslinking.